Embracing the Extend Platform in Postgraduate Education: Unveiling Student Perspectives on Technological Trends in Course Delivery - Hao Tran; Annita Stell; Noriko Iwashita (Trends in Higher Education, 2023)
Recent global events have made it crucial for higher education to continuously update course content with digital alternatives to meet evolving student expectations and enhance their learning experience. The extent of course redevelopment varies widely, depending on the specific learning outcomes. While numerous studies investigate the impact of digitally revitalized course materials on tertiary students, less is known about the user experiences of international postgraduate students in the context of a second language teaching methodology course using different delivery modes. Our study examined postgraduate students’ perceptions of Extend using the Technology Acceptance Model 2 (TAM 2). Extend is an online platform implemented as the main course delivery platform in two postgraduate courses at a large urban Australian university. The results from mid-term evaluation surveys and end-of-semester course evaluations indicated that most students had positive attitudes towards Extend, finding it beneficial for content inclusivity and course objective transparency. The findings highlight both the perceived usefulness and ease of use for building their independent learning journey. However, for a long-term successful learning outcome in delivering this platform across various class deliveries, other aspects related to individual differences need to be taken into consideration.